Examination of sustainability reporting practices in Indian banking sector - Kishore Kumar; Ajai Prakash (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2019)
Sustainability reporting is at the core of designing corporate sustainability environment. The study has been conducted on Indian banking sector to examine the extent of sustainability reporting by the banks operating in India. Sustainability report, corporate social responsibility report, business responsibility report and annual report (FY 2015-16 & 2016-17) of the banks were analysed and coded using content analysis technique against sustainability indicators derived from review of literature, GRI G4 guidelines, and National Voluntary Guidelines on responsible business conduct. This is one of the first studies to examine the extent of sustainability reporting by the commercial banks in India in line with major sustainability-related standards & guidelines. The result of the study shows that the banks in India are much slower in adopting sustainability reporting practices. It was found that sustainability issues which are of the highest priorities for the banks are directly related to their business operations like financial inclusion, financial literacy, energy efficient technology etc. The environmental consideration indicators are relatively unaddressed by most of the banks in India. The results of the study also show that there is a significant difference in the disclosure of environmental and internal socio-environmental indicators between public and private sector banks in India. This study is expected to contribute to banking sector and all the stakeholders in understanding more about the limitations in implementing sustainable reporting in India.
Keywords: 650; Sustainability reporting; GRI; UNGC principles; Sustainable banking; NVGs; Corporate social responsibility